SOSIALISASI PENERAPAN METODE AVERAGE COST DALAM SISTEM PERSEDIAAN AKUNTANSI SEBAGAI STRATEGI PENGEMBANGAN USAHA UMKM - Wulandari, Putri; Chaniago, Ricka Hidayat (Jurnal Pajak Populis, 2025)
This community service program aims to enhance the understanding and practical skills of Micro, Small, and Medium Enterprises (MSMEs) in Desa Purut, Serang Regency, in applying the Average Cost method within inventory accounting systems. The primary issue faced by partner MSMEs is the absence of structured inventory records, which leads to inaccuracies in cost of goods sold calculation and pricing decisions. The program was implemented through an educational and participatory approach, encompassing the socialization of basic inventory accounting concepts, interactive counseling sessions, demonstrations of Average Cost calculations, and hands-on assistance in inventory recording using local business case examples. The results indicate an improvement in participants’ understanding of cost of goods sold determination and the ability to manage inventory in a more systematic manner. Participants also developed a better awareness of the relationship between inventory recording, operational efficiency, and the preparation of simple financial statements. Overall, this program provides tangible benefits for MSMEs by improving business management quality, enhancing decision-making accuracy, and strengthening financial administrative readiness as a foundation for sustainable business development.